2019
DOI: 10.1002/art.40852
|View full text |Cite
|
Sign up to set email alerts
|

Complex Relationships of Smoking, HLA–DRB1 Genes, and Serologic Profiles in Patients With Early Rheumatoid Arthritis: Update From a Swedish Population‐Based Case–Control Study

Abstract: Objective Smoking is associated with an increased risk of rheumatoid arthritis (RA) in subsets of patients defined according to the presence or absence of anti–citrullinated protein antibodies (ACPAs) and rheumatoid factors (RFs). Moreover, an interaction between smoking and the HLA–DRB1 shared epitope (SE) has been demonstrated to be a risk factor for seropositive RA. The aim of this study was to investigate the interplay between smoking and the HLA–DRB1 SE with regard to risk of RA in different patient subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…A breakthrough in RA research occurred with the discovery that antibodies previously defined as anti-perinuclear, antikeratin or anti-filaggrin antibodies displayed a distinct reactivity with peptides and proteins modified by citrullination, later named anti-citrullinated protein/peptide antibodies (ACPA) [11,12]. The presence of these antibodies as measured by the standard anti-circular citrullinated peptides (anti-CCP) assay [13] was mainly seen in the IgM RF-positive group, but there are also smaller subsets of patients who are RF+/anti-CCP-and anti-CCP+/RF- [14][15][16]. Whereas the anti-CCP assay captures most ACPAs, there is a notable heterogeneity in reactivity to distinct citrullinated peptides and proteins with a large number of overlapping subsets being formed [17][18][19][20] (see also Figure 1).…”
Section: Subdivision Of Ra In Subsets By Means Of Serologymentioning
confidence: 99%
See 1 more Smart Citation
“…A breakthrough in RA research occurred with the discovery that antibodies previously defined as anti-perinuclear, antikeratin or anti-filaggrin antibodies displayed a distinct reactivity with peptides and proteins modified by citrullination, later named anti-citrullinated protein/peptide antibodies (ACPA) [11,12]. The presence of these antibodies as measured by the standard anti-circular citrullinated peptides (anti-CCP) assay [13] was mainly seen in the IgM RF-positive group, but there are also smaller subsets of patients who are RF+/anti-CCP-and anti-CCP+/RF- [14][15][16]. Whereas the anti-CCP assay captures most ACPAs, there is a notable heterogeneity in reactivity to distinct citrullinated peptides and proteins with a large number of overlapping subsets being formed [17][18][19][20] (see also Figure 1).…”
Section: Subdivision Of Ra In Subsets By Means Of Serologymentioning
confidence: 99%
“…Later, also the second most prominent genetic variant association with RA, a missense variation in the PTPN22 gene [39] was also found to be mainly associated with ACPA-positive RA [40,41]. Further detailed analysis of the effects of HLA-DR genes in subsets defined combinations of RF and anti-CCP antibodies have shown that the association with HLA-DR SE alleles is confined to subsets of disease that are anti-CCP+/RF+ or anti-CCP+/RF-negative but are not present in the anti-CCP-/RF+ subset, implicating different pathogenic mechanisms in the single RF-positive as compared to the anti-CCPpositive subsets (more about the functional implications of these findings below) [16].…”
Section: Geneticsmentioning
confidence: 99%
“…The idea of directly linking smoking with the breach of tolerance against citrullinated proteins is of high interest; however, this relationship may be more complicated. In several more recent studies, the association between smoking and ACPA was not specific for ACPA, but found to be largely due to the co-occurrence of ACPA and RF, as smoking is associated with RF rather than ACPA 125,126 or with double positivity alone. 127 In ACPA-positive patients with lung disease and without signs of joint inflammation, smoking was not associated with higher ACPA titers or transition toward RA.…”
Section: Smoking and Citrullinated Antigensmentioning
confidence: 98%
“…In this issue of Arthritis & Rheumatology , Hedström and colleagues carefully dissect the links between smoking and the shared epitope to RF and ACPAs by analyzing 4 subsets of rheumatoid arthritis: CCP−RF−, CCP+RF−, CCP−RF+, and CCP+RF+ disease . They demonstrate that nonsmokers with the shared epitope have no significant increased risk of developing CCP−RF+ rheumatoid arthritis but do have an increased risk of developing CCP+RF− rheumatoid arthritis.…”
mentioning
confidence: 99%
“…Finally, further studies are needed to clarify the intersection of the microbiome and mucosal inflammation with ACPAs and RF. Thus, the study by Hedström and colleagues brings us one step closer to understanding the pathophysiology of rheumatoid arthritis and opens the door for many more exciting discoveries.…”
mentioning
confidence: 99%